Frequency of Hypokalemia in Patients with Acute Myocardial Infarction Admitted to the Cardiology Unit of Peshawar Institute of Cardiology, Hayatabad - Farhat Shireen, Maryum Masoud, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of hypokalemia in patients with acute myocardial infarction admitted to the cardiology unit of Peshawar Institute of Cardiology, Hayatabad. Study design: Cross sectional descriptive study. Setting: Cardiology Department, Peshawar Institute of Cardiology, Hayatabad. Duration of study: 6 months (05 August, 2020 to 05 February, 2021) Material & Methods: In the present study a total of 217 patients were observed. Detail history, routine investigation i.e. ECG was done for the confirmation of acute myocardial infarction. From all the patients, 5cc of venous blood was obtained and sent to hospital laboratory to detect hypokalemia. All the laboratory investigations were done under supervision of same consultant pathologist having minimum of five years of experience. hypokalemia was considered positive if the serum potassium concentration is < 3.5 mmol/L on serum electrolyte levels. Results: In this study mean age was 68 years with standard deviation ± 8.04. 132(61%) patients were male while 85(39%) patients were female. Hypokalemia was analyzed as 20(9%) patients had Hypokalemia and 197(91%) patients didn’t had Hypokalemia. Conclusion: Our study concludes that the frequency of hypokalemia was 9% in patients with acute myocardial infarction admitted to the Cardiology Department, Peshawar Institute of Cardiology, Hayatabad. Keywords: Hypokalemia, Diabetic Mellitus, Hypertension, Smoking, Acute Myocardial Infarction